Napisy filmowe jako źródło ekwiwalentów przekładowych w polsko-czeskim korpusie równoległym InterCorp - Charciarek, Andrzej (Studia Rossica Posnaniensia, 2021)
The article focuses on using film subtitles in the process of establishing Polish-Czech language pairs. Research material comes from the resources of the OpenSubtitles website with non-professional subtitling. The research material was analysed using KonText – the main search tool in InterCorp. As a starting point, the author analysed a dictionary entry for the Polish exclamation cholera in a traditional Polish translation dictionary like Polish-Czech Dictionary (Oliva). It presents translation equivalents in translation pairs such as cholera – sakra, hergot, do cholery – do hajzlu, idź do cholery – táhni ke všem čertům, do jasnej cholery – k sakru, do hajzlu, cholera mnie bierze – čerti mě berou. All the translation equivalent pairs have been analysed using the corpus analysis with three functionalities available in the KonText search engine: type of question (typ dotazu), content of the equivalent (obsahuje), and limiting search (omezit hledání). The conducted corpus analysis allowed for the verification of information in the traditional dictionary, but also to find new equivalents that have not been registered yet which could also be used in translation.